THE PAST AND CONTEMPORARY HISTORY OF THE UZBEK NATIONAL INSTRUMENT: DOIRA. - Rajabova Fazolat Zavqiddin qizi, (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
The doira is not merely a percussion instrument but a symbol of Uzbek cultural identity and spiritual heritage. This article explores the historical evolution of the doira, tracing its roots from ancient archaeological findings to its pivotal role in classical Maqom and contemporary music. Through a qualitative analysis of historical texts and modern musical practices, the study highlights how the instrument has transitioned from a ritualistic tool to a professional concert instrument. The findings emphasize the importance of “Ustoz-Shogird” (Master-Apprentice) traditions in preserving its complex rhythmic patterns (“usuls”) in the 21st century.